Promoting the proper use of medicines in rural school children of India - Bankar, Mangesh A.; Dudhgaonkar, Sujata S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The problem of irrational use of medicines is prevalent in rural India. For safe and proper use of medicines there is a need to understand the proper way of taking medicines. Teaching proper use of medicines is the most neglected domain of the school health curriculum. So this study targeted school going children in rural area of India as the earlier the intervention, the more firmly longer lasting health related behavior can be successfully inculcated. The objectives of the study were (1) To study base level knowledge about use of medicines and (2) To implement and see the effect of an intervention to increase medicine knowledge in the form of information, education and communication (IEC) in rural school children. Methods: This was an interventional, questionnaire based (quantitative) study in which an intervention in the form of lectures which was given to school children. Rural school going children in age group of13-15 years were selected from 3 different schools of rural areas of Nagpur district, India. 500 school children were included after obtaining permission from school authorities and informed consent from their parents. Pretesting done by administering a questionnaire containing 20 questions to assess children’s base level knowledge about medicine use. The same questionnaire was repeated on 16th and 45th day of intervention i.e. daily lectures of 25-30 minutes for 15 days on proper use of medicines, to judge the improvement. Results: It was observed that the interventions brought about a positive change in the knowledge of the students as well as increased awareness about proper use of medicines. Conclusions: This study showed that properly timed and meticulously implemented intervention can bring about a positive change in the attitude and knowledge of school children.